Empirical Evaluation of the Effectiveness of Janani Shishu Suraksha Yojana (JSSY): A Case Study of Rajasthan : जननी शिशु सुरक्षा योजना की प्रभावशीलता का अनुभवमूलक मूल्यांकन - राजस्थान के सन्दर्भ में - Gupta, Govind (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Janani Shishu Suraksha Yojana (JSSY) is a significant maternal and child welfare scheme launched by the Government of India. Its primary objective is to provide safe delivery, free healthcare services, and essential facilities to pregnant women belonging to poor and marginalized sections of society. This research aims to understand the actual effectiveness of the scheme in the state of Rajasthan based on the experiences of its beneficiaries. The study found that the scheme has encouraged rural women to opt for institutional deliveries, contributing to a reduction in maternal and infant mortality rates. Free transportation, meals, medicines, and care services have proven to be highly beneficial for women. However, challenges such as poor service quality in certain areas, lack of staff, limited awareness, and lack of transparency in service delivery were also reported. In particular, inadequate promotion and lack of information about the scheme’s benefits have prevented many eligible women from availing its advantages. Abstract in Hindi Language: जननी शिशु सुरक्षा योजना (JSSY) भारत सरकार द्वारा प्रारंभ की गई एक महत्वपूर्ण मातृ एवं शिशु कल्याण योजना है, जिसका उद्देश्य निर्धन एवं वंचित वर्ग की गर्भवती महिलाओं को सुरक्षित प्रसव, निःशुल्क स्वास्थ्य सेवाएं एवं आवश्यक सुविधाएं प्रदान करना है। यह शोध राजस्थान राज्य में इस योजना की वास्तविक प्रभावशीलता को लाभार्थियों के अनुभवों के आधार पर समझने का प्रयास करता है। अध्ययन में पाया गया कि योजना ने ग्रामीण महिलाओं को संस्थागत प्रसव की ओर आकर्षित किया, जिससे मातृ एवं शिशु मृत्यु दर में कमी आई है। मुफ्त परिवहन, भोजन, दवाएं एवं देखभाल सेवाएं महिलाओं के लिए अत्यंत सहायक सिद्ध हुई हैं। हालांकि, कुछ क्षेत्रों में स्वास्थ्य सेवाओं की गुणवत्ता, कर्मचारियों की अनुपलब्धता, जागरूकता की कमी एवं सेवा प्रदायगी में पारदर्शिता का अभाव जैसी समस्याएं भी सामने आईं। विशेष रूप से योजना के प्रचार-प्रसार और लाभों की जानकारी का अभाव कई पात्र महिलाओं को इसका लाभ उठाने से वंचित कर देता है। Keywords: जननी शिशु सुरक्षा योजना, मातृत्व स्वास्थ्य, संस्थागत प्रसव, अनुभवमूलक मूल्यांकन